Quantifying the Impact of Al Deposition Method on Underlying Al2O3/Si Interface Quality - Mack Iris; Rosta Kawa; Quliyeva Ulviyya; Ott Jennifer; Pasanen Toni P; Vähänissi Ville; Jahanshah Rad Zahra Sadat; Lehtiö Juha-Pekka; Laukkanen Pekka; Soldano Caterina; Savin Hele (WILEY-V C H VERLAG GMBH, 2025)
Oxide-semiconductor interface quality has often a direct impact on the electrical properties of devices and on their performance. Traditionally, the properties are characterized through metal-oxide-semiconductor (MOS) structures by depositing a metal layer and measuring the capacitance-voltage (C-V) characteristics. However, metal deposition process itself may have an impact on the oxide and the oxide-semiconductor interface. The impact of magnetron sputtering, e-beam evaporation, and thermal evaporation on an Al2O3/Si interface is studied, where atomic layer deposited (ALD) Al2O3 is used, by MOS C-V and corona oxide characterization of semiconductors (COCOS) measurements. The latter allows characterization of the interface also in its original state before metallization. The results show that sputtering induces significant damage at the underlying Al2O3/Si interface as the measured interface defect density Dit increases from 10(11 )to 10(13) cm (-2) eV. Interestingly, sputtering also generates a high density of positive charges Qtot at the interface as the charge changes from -2 x 1012 to +7 x 1012 cm-2. Thermal evaporation is found to be a softer method, with modest impact on Dit and Qtot. Finally, Alnealing heals the damage but has also a significant impact on the charge of the film recovering the characteristic negative charge of Al2O3 (--4 x 10(12) cm(-2)).